Multi-objective decision analysis managing trade-offs and uncertainty - Brownley, Clinton W. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
Whether managing strategy, operations, or products, making the best decision in a complex, uncertain business environment is challenging. One of the major difficulties facing decision makers is that they often have multiple, competing objectives, which means trade-offs will need to be made. To further complicate matters, uncertainty in the business environment makes it hard to explicitly understand how different objectives will impact potential outcomes. Fortunately, these problems can be solved with a structured framework for multiobjective decision analysis that measures trade-offs among objectives and incorporates uncertainties and risk preferences. This book is designed to help decision makers by providing such an analysis framework implemented as a simple spreadsheet tool. This framework helps structure the decision-making process by identifying what information is needed in order to make the decision, defining how that information should be combined to make the decision, and, finally, providing quantifiable evidence to clearly communicate and justify the final decision. The process itself involves minimal overhead and is perfect for busy professionals who need a simple, structured process for making, tracking, and communicating decisions. With this process, decision making is made more efficient by focusing only on information and factors that are well defined, measureable, and relevant to the decision at hand. The clear characterization of the decision required by the framework ensures that a decision can be traced and is consistent with the intended objectives and organizational values. Using this structured decision-making framework, anyone can effectively and consistently make better decisions to gain a competitive and strategic advantage.
Acknowledgments -- 1. Introduction to multiobjective decision analysis -- 2. Structuring objectives and developing alternatives -- 3. Value functions and preference weights -- 4. Uncertainty: probability distributions and expected value -- 5. Uncertainty: risk tolerance and expected utility -- 6. Multiobjective decision analysis under uncertainty -- 7. Conclusion -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (p. 151-156) and index.
Also available in print.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Keywords: Multiple criteria decision making; decision making; decision analysis; decision modeling; strategic decisions; business decisions; how to decide; trade-offs; multiobjective; values; weights; value functions; objectives; measures; alternatives; uncertainty; probability; discrete; continuous; linear; exponential; expected value; utility; expected utility; risk tolerance; certainty equivalents; Electronic books